A population of CD4hiCD38hi T cells correlates with disease severity in patients with acute malaria. Issue 11 (24th November 2020) - Apte, Simon H; Minigo, Gabriela; Groves, Penny L; Spargo, Jessie C; Plebanski, Magdalena; Grigg, Matthew J; Kenangalem, Enny; Burel, Julie G; Loughland, Jessica R; Flanagan, Katie L; Piera, Kim A; William, Timothy; et al.
Abstract: Objective: CD4 + T cells are critical mediators of immunity to Plasmodium spp. infection, but their characteristics during malarial episodes and immunopathology in naturally infected adults are poorly defined. Flow cytometric analysis of PBMCs from patients with either P. falciparum or P. knowlesi malaria revealed a pronounced population of CD4 + T cells co‐expressing very high levels of CD4 and CD38 we have termed CD4 hi CD38 hi T cells. We set out to gain insight into the function of these novel cells. Methods: CD4 + T cells from 18 patients with P. falciparum or P. knowlesi malaria were assessed by flow cytometry and sorted into populations of CD4 hi CD38 hi or CD4 norm T cells. Gene expression in the sorted populations was assessed by qPCR and NanoString. Results: CD4 hi CD38 hi T cells expressed high levels of CD4 mRNA and canonical type 1 regulatory T‐cell (TR1) genes including IL10, IFNG, LAG3 and HAVCR2 (TIM3), and other genes with relevance to cell migration and immunomodulation. These cells increased in proportion to malaria disease severity and were absent after parasite clearance with antimalarials. Conclusion: In naturally infected adults with acute malaria, a prominent population of type 1 regulatory T cells arises that can be defined by high co‐expression of CD4 and CD38 (CD4 hi CD38 hi ) and that correlates with disease severity in patients with falciparum malaria. This study provides fundamental insights into T‐cell biology, including the first evidence that CD4 expression is modulated at the mRNA level. These findings have important implications for understanding the balance between immunity and immunopathology during malaria. Abstract : In this study, we identified a population of CD4 + T cells that expresses very high levels of CD4 and CD38 (CD4 hi CD38 hi ) in adult malaria patients living in malaria‐endemic regions. These cells were increased in proportion to disease severity, and gene expression analysis revealed them to be type 1 regulatory T cells. Increased CD4 co‐receptor surface expression by CD4 hi CD38 hi T cells was modulated at the mRNA level revealing a level of commitment to the phenotype and a hitherto unseen mechanism by which CD4 T cells may potentially modulate their activity.